Trend of Changes in Chloramphenicol Resistance during the Years 2017-2020: A Retrospective Report from Israel - Hannan Rohana; Anat Hager-Cohen; Maya Azrad; Avi Peretz (MDPI AG, 2023)
Resistant bacteria limit treatment options. This challenge has awakened interest in antibiotics that are no longer in use due to side effects, such as chloramphenicol. This work investigated trends in chloramphenicol resistance rates during 2017-2020 in bacteria isolated from diverse clinical samples at the Baruch Padeh Medical Center, Poriya, Israel. Bacteria were isolated from 3873 samples and identified using routine methods, including matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) technology. Chloramphenicol susceptibility was tested using a VITEK II instrument or by the Kirby-Bauer disk-diffusion test. The average chloramphenicol resistance rate was 24%, with no significant differences between study years. Chloramphenicol resistance was associated with sample origin (p < 0.001); isolates originating from sputum samples showed 49.8% resistance rate, compared to 2.3% of the body fluid isolates, 10.4% of the ear/eye isolates and 22.5% of the blood isolates. Furthermore, there was a significant decrease in chloramphenicol resistance among blood and ear/eye isolates during the study period (p = 0.01, p < 0.001, respectively). The highest resistance rate was among Pseudomonas aeruginosa isolates (50.5%). In conclusion, since chloramphenicol susceptibility seems to be retained, its comeback to the clinical world should be considered.